2019
DOI: 10.3390/catal9060536
|View full text |Cite
|
Sign up to set email alerts
|

Cu Modified Pt Nanoflowers with Preferential (100) Surfaces for Selective Electroreduction of Nitrate

Abstract: Improving surface selectivity and maximizing electrode surface area are critical needs for the electroreduction of nitrate. Herein, preferential (100) oriented Pt nanoflowers with an extended surface area were prepared by potentiostatic deposition on carbon cloth (Pt NFs/CC), and then Cu atoms were adsorbed on the Pt NFs (Cu/Pt NFs/CC) for application of nitrate electroreduction. The results reveal that Cu/Pt NFs/CC with 8.7% Cu coverage exhibits a high selectivity for nitrate electroreduction to N2 following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This indicates that Cu atoms enhance electrocatalytic NO 3 RR activity. The enhanced NO 3 RR activities by introducing Cu into Co is well-agreed with literatures, in which Cu acts as a promoter to improve initial reduction pathway of NO 3 – to NO 2 – …”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates that Cu atoms enhance electrocatalytic NO 3 RR activity. The enhanced NO 3 RR activities by introducing Cu into Co is well-agreed with literatures, in which Cu acts as a promoter to improve initial reduction pathway of NO 3 – to NO 2 – …”
Section: Results and Discussionsupporting
confidence: 89%
“…This indicates that introducing Cu atoms enhances the initial NO 3 RR step (NO 3 – + H 2 O + 2e – → NO 2 – + 2OH – ). Because the NO 2 – formation is also considered as a rate-limiting step in NO 3 RR to NH 3 (or N 2 ), replacing Co with Cu could reduce the NO 3 RR overpotential.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Chen et al prepared Cu-modified Pt nanoflowers with preferential (100) surfaces by potentiostatic deposition on C cloth (Cu/Pt NFs/CC) for selective nitrate reduction. 151 The obtained Cu/Pt NFs/CC with 8.7% Cu coverage exhibited a nitrate removal of 77.5% and N 2 selectivity of 72.9%. Additionally, Mumtarin et al recently reported the applicability of an oxide deficit (OD) Pt-Cu catalyst as a nitrate sensor by electrodeposition method.…”
Section: Screening Of Nitrate Reduction Electrocatalysts In Aqueous S...mentioning
confidence: 88%
“…In the implementation of the construction of cathode, porous substrates, such as Ni foam, [85,87,[135][136][137][138] Cu foam, [31,139] and carbon fiber products [140,141] can generate high surface area for the hosting of active sites. Moreover, the tunable porosity in these substrates strongly influences both the process performance and product distribution.…”
Section: Dimensional Stability Of Cathodementioning
confidence: 99%